2018
DOI: 10.1038/s41598-018-21413-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of methane production from Cotton Stalk using different pretreatment techniques

Abstract: China produces large amount of cotton stalk (CS) residues as agricultural biomass, which are incinerated on-site, causing air pollution. The high organic content of CS could be utilized for biogas production, but the direct digestion without pretreatment always leads to a low methane yield and biodegradability, due to the complicated structure of lignocellulose. In order to search best fitting pretreatment methods in effective anaerobic digestion (AD) of CS, effects of various pretreatments including KOH, NaOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 33 publications
6
20
1
1
Order By: Relevance
“…This process also has the advantage of not leaving H 2 O 2 residue, and it is considered as an environmentally friendly and low-cost application [ 22 ]. While a large number of studies were conducted using alkaline H 2 O 2 pretreatment on various types of agricultural waste, such as corn stover, wood waste, soft wood, cashew apple bagasse, energy crops, sugar cane bagasse, agricultural crop stalks, and cotton stalks [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], this method, although quite promising, remains untested for greenhouse crop wastes.…”
Section: Introductionmentioning
confidence: 99%
“…This process also has the advantage of not leaving H 2 O 2 residue, and it is considered as an environmentally friendly and low-cost application [ 22 ]. While a large number of studies were conducted using alkaline H 2 O 2 pretreatment on various types of agricultural waste, such as corn stover, wood waste, soft wood, cashew apple bagasse, energy crops, sugar cane bagasse, agricultural crop stalks, and cotton stalks [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], this method, although quite promising, remains untested for greenhouse crop wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion is a sequential process in which diverse microbial communities including hydrolytic, acidogenic, and acetogenic bacteria and methanogenic archaea interact mutually [9]. The lignocellulosic structures of agro-residues limit the hydrolysis rates which then affect the methane yields [9,25,26]. Thus, appropriate inoculum should be used during the start-up period which includes necessary microbial communities having an ability to degrade lignocellulosic feedstock.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, three studies reported combined processes to be low energy-consuming. This observation was sustained byKumar and Sharma (2017),Zhang et al (2018), andKim et al (2019). It can be postulated that this variation in results is due to the complexity of combined methods and further research is needed.…”
mentioning
confidence: 85%